Vertical Cancer Transmission via Asexual Fragmentation and Associated Cancer Prevalence - Jibeom Choi (Evolutionary Applications)
ABSTRACT While sexual reproduction is a general feature of animals, fissiparity and budding are relatively uncommon modes of asexual reproduction by which a fragment from a parent becomes an independent organism. Unlike unitary development, tumor cells can be included in the detached fragment destined to become offspring. Although fragmentation facilitates the vertical transmission of parental tumor cells to nascent progeny, this process requires significantly fewer cell replications than development from a zygote. The former is a risk factor for cancer, while the latter reduces oncogenic mutations during replication, indicating that two opposite effects of carcinogenesis are involved in fragmentation. If fragmentation can significantly reduce the number of cell replications for the development and a small portion of parental cancer is transmitted to the offspring during fragmentation, consecutive fragmentation across generations can gradually diminish the cancer risk of offspring, which I term fragmentational purging. On the other hand, consecutive fragmentation may aggravate the cancer risk of the progeny, a process of fragmentational accumulation. The model results imply that fragmentational purging does not necessarily guarantee the evolution of fragmentation, nor does fragmentational accumulation ensure its exclusion. Other relevant factors including juvenile susceptibility of sexual reproduction and loss of genetic diversity stemming from asexual reproduction can influence the selective advantage of fragmentation. Furthermore, owing to the common features of stemness and self‐renewal, the existence of pluripotent adult stem cells required for fragmentation could be coupled with elevated cancer risk. The model results across diverse parameters and the associated mathematical analyses highlight multifaceted evolutionary trajectories toward fragmentation. Further investigation of cancer‐suppression strategies that fragmentational animals employ could provide insights into regenerative medicine and cancer therapy.